The link between anemia and adverse outcomes in patients with acute coronary syndrome. (4th March 2019) - Guedeney, Paul; Sorrentino, Sabato; Claessen, Bimmer; Mehran, Roxana
ABSTRACT: Introduction : Anemia is one of the most frequent comorbidities in acute coronary syndrome (ACS) patients and is associated with a significant impact on clinical outcomes. This review summarizes the knowledge and updated management of anemia in the setting of ACS. Areas covered : We provide a review on the prevalence, pathophysiology, prognosis, impact, and updated management of anemia. Expert opinion : Patients with anemia represent a therapeutic challenge in the setting of acute coronary syndrome and require specific acute and chronic management. Despite the high prevalence of anemia and the large amount of data confirming its strong impact on short- and long-term outcomes, a commonly used and accurate definition in the context of patients undergoing percutaneous coronary intervention and stent implantation for ACS is still lacking. Furthermore, therapeutic options to address anemia remain limited. The combined use of risk scores to identify high-risk characteristics for adverse bleeding or thrombotic events may guide individualized treatment of anemic patients, for example, by selecting an antiplatelet regimen aimed at minimizing bleeding or thrombotic risk. The optimal strategy for blood transfusion is currently being evaluated by an ongoing randomized trial.